Class III Orthodontic Camouflage: Is the “Ideal” Treatment Always the Best Option? A Documented Case Report - Lorenzo Rustico; Vincenzo Ronsivalle; Flavia Iaculli; Gianrico Spagnuolo; Gaetano Isola; Antonino Lo Giudice (Case Reports in Dentistry)
Angle’s Class III is one of the most complex malocclusions to treat. In nongrowing skeletal class III malocclusions, the choice between orthognathic surgery and camouflage treatment remains a challenge to the orthodontist. In class III borderline cases, clinicians are called to find the best compromise between functional and aesthetics outcomes, with the latter which often turns in avoiding worsening of profile characteristics, which makes the treatment of these patients quite challenging. This case report describes a borderline nongrowing patient with skeletal class III malocclusion, upper incisor proclination and spacing, lower crowding, and arch width discrepancy, which has already undergone previous orthodontic treatment. The orthodontic treatment involved the mandibular first premolar extraction, resulting in class I canine relation with good overjet and overbite as well as good arch coordination. The orthodontic camouflage improved the dental relationship with normalization of upper incisor inclination without a relevant retroclination of lower incisors; the skeletal facial pattern of the patient experienced a slight improvement. The tendency to skeletal class III has remained nearly unaffected. Treatment outcomes were stable after 1-year posttreatment follow-up.